Journalism : theory and practice - Detrani, Jason R. , 1965- (Apple Academic Press, 2011)
"[This book] presents a short history of journalism and focuses on the many important issues facing the media today, including bridging the divide between science and journalism; issues in and public perception of war reporting; the ethics and procedures of media coverage of natural disasters; the current difficulties facing U.S. newspapers; an in-depth analysis of how news organizations report new medical treatments, tests, products, and procedures; and more. The book also includes a history of and tribute to Edward R. Murrow, a pioneer in the field of television news broadcasting, including a report of how Murrow used the new media of his time, first radio, and then television. A comprehensive overview of running a government press office is presented as well"